PENGARUH BIG FIVE PERSONALTY TERHADAP PERILAKU AGGRESSIVE DRIVING PENGEMUDI DEWASA AWAL DI UNIVERSITAS NEGERI MAKASSSAR - Suci Wulandari; Asniar Khumas; Faradillah Faradillah (Cross-border, 2022)
Adult beginner drivers in the range of 18-22 years old are oftenly found violating traffic rules which could lead to physical or mental harm is a characteristic indicated as Aggressive Driving. The aggressive driving is caused by an individual behavior and big five personality. The purpose of this research is to find out the influence of the big five personalities (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism) on aggressive driving on the adult beginner driver of Universitas Negeri Makassar. There are 323 Universitas Negeri Makassar’s students who are involved in this research. The purposive sampling method is used to determine the samples taken. On other hand, the validity used is the scale of the big five personalities. This research used the simple regression test analysis method. The results of this study indicate that the openness to experience personality type has an influence with aggressive driving (r= 0.690, p = 0.000), the conscientiousness personality type does not affect aggressive driving (= 0.692, p = 0.275), the extraversion personality type has an aggressive effect. driving (r= 0.741 p = 0.000), agreeableness personality type has an influence with aggressive driving (r= 0.746, p = 0.030), and neuroticism personality type has no influence with aggressive driving (r= 0.741, p = 0.780). The results of this research could be used as an insight to confirm that aggressive driving behavior found in adult beginner drivers could be observed basic on the type of personality that each individual possessed.